2023
DOI: 10.2351/7.0000903
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of precession laser machining of microholes in aerospace material

Abstract: Sidewall tapering is one of the main limitations in ultrashort pulse (USP) laser machining and is associated with the beam shape and self-limiting effect. Laser processing with a precession beam is a potential solution to overcome this limitation. A study into the effects of precession parameters on the taper angle in microhole drilling of a nickel alloy is reported in this paper. The effects of three key precession parameters, i.e., incident angle, relative distance between the focuses of the precession and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Le et al investigated the effects of three key parameters, the angle of incidence, FPB-FIB distance, and scanning speed, on the feed laser drilling process. The results showed that an increase in the angle of incidence and FPB-FIB distance led to a decrease in the taper angle, and, conversely, an increase in the scanning speed led to an increase in the taper angle [20]. Sun et al explored the microhole processing of an In718 thermal barrier coating using a picosecond laser, thereby investigating the correlation between thermal accumulation and process parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Le et al investigated the effects of three key parameters, the angle of incidence, FPB-FIB distance, and scanning speed, on the feed laser drilling process. The results showed that an increase in the angle of incidence and FPB-FIB distance led to a decrease in the taper angle, and, conversely, an increase in the scanning speed led to an increase in the taper angle [20]. Sun et al explored the microhole processing of an In718 thermal barrier coating using a picosecond laser, thereby investigating the correlation between thermal accumulation and process parameters.…”
Section: Introductionmentioning
confidence: 99%